A CEPHALOMETRIC STUDY TO EVALUATE AND COMPARE THE EFFECT OF UPPER PREMOLAR EXTRACTION ON PHARYNGEAL AIRWAY DIMENSION IN SKELETAL CLASS I AND CLASS II PATIENTS - Paul, Rahul; Yadav, Deepti; Kishore, Priya; Kumar Sharma, Ish; Gulia, Vandana; Saini, Prakher (International Journal of Research -GRANTHAALAYAH, 2025)
The goal of this study was to evaluate and compare the effect of upper premolar extraction on pharyngeal airway dimension in skeletal class I and class II malocclusion patients. This retrospective study analyzed pre- and post-treatment orthodontic records of patients with skeletal Class I and Class II malocclusions to assess changes in the pharyngeal airway. ANB and WITS appraisal was employed to determine the skeletal pattern. Measurement parameters of Pharyngeal airway dimensions like superior, middle and inferior airway space were evaluated and compared between the two malocclusions. Lateral cephalograms of 100 patients (50 with Class I and 50 with Class II malocclusion) aged 18–26 years were used to measure airway dimensions, and data was compared to evaluate the impact of orthodontic treatment on pharyngeal space. Pre- and post-treatment cephalograms were obtained using standardized exposure settings and patient positioning. The data was analyzed using software SPSS 27.0 with Non-parametric test and the Wilcoxon signed-rank test at a 5% significance level was used. The results indicated that pharyngeal airway dimensions in skeletal Class I patients had a wider airway than Class II patients. Also, before treatment, Class I malocclusion patients had a wider pharyngeal airway than Class II patients while After-treatment, both groups experienced airway reduction, with Class I patients showing a more significant decrease.